Penerapan Metode Demonstrasi Melalui Media Audiovisual Untuk Meningkatkan Hasil Belajar Ipapeserta Didik Kalas I Sdn 5 Bengkalis Kabupaten Bengkalis Tahun 2016 - Elnaledy Elnaledy (Akademika: Jurnal Keagamaan dan Pendidikan, 2017)
Class Action research with the title “Implementation Demonstration methods through Audio Visual Media to improve the results of the learning science learners Class I SD Negeri 5 Bengkalis “ written by Hj Elnaledy, S.Pd.SD Research was based on by the existence of its problem faced in the learning process in SD Negeri 5 Bengkalis learners weak in self and the understanding of the material that is taught by the teacher and especially Buddhists. Because learners consider Science subjects much material that must be made ritual and must be applied. Addressing these problems, need to be developed appropriate learning methods and effective methods of demonstration through audio visual media that can improve the results of the study learners. The formulation of the problem in the writing of the PTK is: (1) How the implementation of the demonstration method can improve the results of the study IPApeserta students of SD 5 Bengkalis. (2) How the results of the learning science students of SD 5 Bengkalis after using the method demonstration through audio visual media. The objective of this research is (1) to explain the implementation of the method demonstration through audio visual media on subjects IIPAmateri Apply how to care for and pray for the sick and train yourself to keep their minds when sick on the students of grade 1 in SD Negeri 5 Bengkalis. (2) to describe the improvement of the learning results obtained learners with the implementation of the method demonstration through audio visual media on the subjects of Buddhism. Research design that is used is a Class Action Research (Class Action Research as much as two cycle. Each cycle consists of four stages namely planning, implementation, observation and reflection. While the collection of data using, test, questionnaires, note the field, and documentation that directly in the field. The source of the data from this research is the learners class I SD Negeri 5 Bengkalis. Data analysis used include data reduction, presentation of data and the withdrawal of the conclusion. Indicators of success in this research when mastering learners reached 75 percent of goals that should be achieved with the value of the KKM 75. The results of the study showed that the results of learning learners has increased from I cycle to the cycle II, namely at cycle I with the value of the average 73,3 (60%) and at cycle II with an average of 80 (85,7%). Based on the results of research, it can be concluded that the implementation of the method demonstration through audio visual media can improve the results of the study of science lesson materials identifying objects in the environment around based on characteristics by observation and know the things that can be changed shape on the class I SD Negeri 5 Bengkalis.